PRODUKSI BIBIT BUAH NAGA DAGING MERAH MELALUI STEK DAN HASIL KULTUR JARINGAN UNTUK PETANI LAHAN KERING DESA SIDERA DAN JONO OGE KECAMATAN SIGI BIROMARU - Zainuddin Basri; Maemunah Maemunah; Hawalina Kasim; Yusran Yusran (Universitas Tadulako, 2018)
Geography and climate of Palu and Sigi Regency has been markedly suitable for dragon fruit supported by the available land in the areas. Unfortunately, development of the commodity has been restricted by less available qualified seedlings and unskill farmers. Dragon fruit seedling production can be achieved through cuttings and tissue culture acclimatized planlets. This program aimed to transfer the technology on cultivation, seedling production through cuttings and tissue culture planlets of dragon fruit, which is turn can increase the income of the farmers. The method used to solve the problems justified were: extension, training and accompaniment on cultivation, seedling production through cuttings and tissue culture planlets acclimatized of dragon fruit. The extension, training and accompaniment were conducted both in class and on farm. The results of this program: The farmers or the program partners understand and become skillful in: dragon fruit cultivation; producing dragon fruit seedlings through cutting and tissue culture planlets acclimatized. The farmers got more than 250 qualified seedlings from tissue culture propagation and 200 seedlings obtained from cuttings grown in a nursery, and the farmers have willingness to be nursery man.